América Latina en El Correo de Ultramar, parte literaria e ilustrada reunidas: literatura de viajes e imaginarios - Beatriz Ferrús Antón (Cuadernos de Ilustración y Romanticismo)
This article analyzes the travel literature to Latin America published by the journal El Correo de Ultramar, parte literaria e ilustrada reunidas (1853-1886), that declared its americanist vocation since its first issue. This paper studies, therefore, different textual typologies included inEl Correo... and dedicated to the continent, as well as themes they cover, lithographs and illustrations going along with them, and the rewriting of Chronicles of the Indias from the perspective of Romanticism, as a set of imaginary strategies that account for complex processes of geopolitical redefinition that would take place in the transatlantic triangle. At the same time, different neocolonial interests were fighting for the region.